2012
DOI: 10.1108/07363761211274992
|View full text |Cite
|
Sign up to set email alerts
|

European football teams' CSR engagement impacts on customer‐based brand equity

Abstract: PurposeBrand management is a central issue for the sports industry in general, and professional football clubs (usually called soccer teams in the USA) are the archetypal branded sport in that industry; the brand is their most important asset. Match attendance equates with financial return; patently it is a preoccupation of senior management. Metrics of brand performance need be up to date, and include contemporary issues such as corporate social responsibility (CSR) as a reflection of consumer expectations. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
43
0
8

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 69 publications
(67 citation statements)
references
References 50 publications
(49 reference statements)
3
43
0
8
Order By: Relevance
“…Purchase behavior of merchandising products and season tickets was included within the scope of research (Blumrodt et al, 2012). The category in assumption is identified by a tick for each of the three (four) categories for the four clubs (cf.…”
Section: Comparing the French And German Spectators' Purchase Intentionsmentioning
confidence: 99%
“…Purchase behavior of merchandising products and season tickets was included within the scope of research (Blumrodt et al, 2012). The category in assumption is identified by a tick for each of the three (four) categories for the four clubs (cf.…”
Section: Comparing the French And German Spectators' Purchase Intentionsmentioning
confidence: 99%
“…Practically Galbreath (2010) provides evidence that when firms display honesty, integrity and fairness through product quality, this behavior is tied to the ethical dimension of a firm's social responsibility and as such reflects CSR activity contributing to competitive advantages and bottom-line positive outcomes. Finally, a recent study by Blumrodt et al (2012) indicated that sport clubs' involvement in CSR activities affects customers behavior and leads to competitive advantages since CSR enhances club's brand image and satisfies stakeholders expectations (being financially stable and abiding to sporting rules and laws). Clubs good and responsible behavior is recognized by the customers which has upcoming positive impacts on clubs' financial performance.…”
Section: H2: Environmentally Responsible Activities Will Have a Positmentioning
confidence: 99%
“…The key players of this sport community are constantly in search for synergies necessary for their function and development. Furthermore, CSR offers the sports world a round table of long term direct communication and interaction since it attracts the attention of both local potential customers but also central authorities, local governments and non-profit sport organizations which inevitably interact towards producing the sports product or service (Walters, 2012;Blumrodt et al, 2012).…”
Section: Business Management and Strategymentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, Walsh and Lee (2012) in a dissertation entitled "Developing decision making model of branding development for the professional sport teams" have found that proposing and managing is a significant strategy for sport teams in regard with creating contact spot between spectators and the team and has this capability to have a positive impact on their beliefs (6). Blumrodt, Bryson, and Flanagan (2012) in their study have arrived to the conclusion that total brand management is considered a key issue in industry, and sport and professional football clubs are acting as a role model in this industry (7). Their brand is their main capital and their presence in competitions is accounted as a return of capital, which indicates management at a high level (7).…”
Section: Introductionmentioning
confidence: 99%